Translation Techniques of Manual Text - Indarti, Dwi (LADU: Journal of Languages and Education, 2021)
Background: Translators often deal with various types of texts, such as academic texts, journalistic texts, subtitle texts, legal texts, speech texts, literary texts, and manual texts. Manual text could be one of many interesting subjects of research in translation field. Translating manual text should follow the principles, such as communicative, short, concise, easy to read, reader-oriented, and natural in target language.Purpose: This study examines the translation technique of 12 excerpt of Cosmos oven manual text in the form of phrases, clauses, and sentences translated from English into Indonesia.Design and Method: Â This study uses 18 translation technique from (Molina Albir, 2002) to analyzed the data that was taken from Cosmos oven manual text.Results: The results of the study showed that there are six translation techniques found in Cosmos oven manual texts: amplification (30%), modulation (26%), reduction (26%), borrowing (7%), literal translation (7%), and linguistic compression (4%). Cosmos oven manual text mostly used amplification technique. There are some additional words or information, paraphrasing, making the text explicit to make the translation clear and help target readers understand the text.